Genealogy of Being in Postcolonial Kazakh Culture: Re-Reading the Words of Edification - Merey Kossyn (Comparative Literature: East & West)
Contemporary post/decolonial discourses in Kazakhstan have completely excluded the following issue from the field of narrative: the question of critically reevaluating the pre-colonial cultural structure. These discourses consider current issues mostly as a result of colonialism and overemphasize external factors. It is important to read and decipher the symbols of the cultural structure to understand the origins of authoritarianism and other socio-political problems. This article aims to investigate the origins of notions of the human being and its existence in the postcolonial Kazakh culture through comparing it to its pre-colonial cultural context. I will be working with Abai’s Words of Edification, which is a collection of texts written in prose in the form of a free philosophical meditation, and it is an apt source for the investigation of the origin of the notion of human existence. The politicization of Abai’s figure starting from the Soviet period and continuing in the postcolonial era obscures the initial questions in the text, and several lines from the Words of Edification engendered the utmost controversy and overshadowed the rest of the text. The aim of this article is to demythologize the poet’s image and focus on symbols hitherto unread.